Assessing the persistence capacity of communities facing natural disturbances on the basis of species response traits. (July 2016) - Sánchez-Pinillos, Martina; Coll, Lluís; De Cáceres, Miquel; Ameztegui, Aitor
Highlights: We present an index to estimate the persistence capacity of communities facing disturbances. The index is based on diversity, abundance and redundancy of species response traits. We illustrate its use in forest of Peninsular Spain and the Balearic Islands. The index is complementary to other functional approaches and easy to use. It is flexible and applicable to different communities affected by any disturbance. Abstract: Adequately assessing the ecosystem resilience and resistance is a challenging and essential question in the current context of widespread environmental change. Here we suggest the use of a quantitative measure we call Persistence Index (PI) to assess the capacity of communities to maintain their functions and services after disturbances. First, we present the formulation of PI that is based on the diversity, abundance, and redundancy of disturbance- and taxon-specific response traits. Then, we use simulated data sets to study the effects of species richness and the number and frequency of traits on PI values. Finally, we illustrate our approach by assessing the persistence capacity of forest communities in Peninsular Spain and the Balearic Islands in response to fire, drought and windstorm events. The Persistence Index was found to be relatively independent on the number of considered traits, but variable according to the frequency of traits in the community. In the evaluation made with national forest inventory data, PI was found to vary within and among different forest types, being particularly high in stands dominated by non-native species (e.g. Eucalyptus sp.) or in mixed-stands composed by evergreen and deciduous broadleaf species. We also found PI values to increase with the number of species present in the stand, although this relationship saturated due to overlap in species response traits. The presented index is complementary to other approaches developed to study the functional structure of communities through the distribution of species in a functional space. It can be applied to a broad spectrum of communities subjected to different types of stressors, making it a useful tool to guide ecosystem management decisions in a context of changing climate and uncertain disturbance regimes.